ICP/XRF Analysis for Trace Elements in Soil Samples from Gezira and Suki Schemes, Sudan (International Journal of Scientific Research and Management (IJSRM), 2021)
In the present study, soil samples have been collected from two different agriculture areas: Gezira and Suki schemes in Sudan, The elemental concentrations for Cr, Ni, Cu, Zn, and Pb have been determined using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and X-ray Fluorescence spectrometry (XRF). The accuracy of measurements has been investigated by using ISE (PT) 1&4 and fortified samples for ICP, IAEA-Soil-7 XRF, respectively. A good agreement was found between certified and measured values. The average elemental concentrations by ICP of these elements Cr, Ni, Cu, Zn, and Pb in loc1 were found as follows: 84.7, 48.15, 33.5, 65.43, and 12.57 ppm, respectively. While the results obtained in loc2 were found as follows: 105, 65.1, 41.3, 55.4, and 12.74 ppm, respectively. The average elemental concentrations by XRF of these elements Cr, Ni, Cu, Zn, and Pb in loc1 were found as follows: 77.21, 43.72, 27.62, 86.96, and 18.74 ppm, respectively. While the results obtained in loc2 were found as follows: 123.33, 57.41, 35.99, 98.85, and 16.43 ppm, respectively. A statistical test (t-test) was applied to the data of both methods without any significant difference between the two techniques. The results obtained were compared to WHO permissible limits. Correlations between different elements were performed. Hierarchical cluster analysis was done for the data. The average elemental concentrations were calculated and compared with data from the literature.